Desirable Family Financial Behaviors: An Examination of the Role of Family Structure in the United States - Yu Zhang; Swarn Chatterjee; Diann C Moorman (Journal of Financial Therapy, 2024)
This study contributes to research on family financial behaviors in the United States by examining the association between various family structures and desirable financial behaviors among American families. Utilizing data from the 2016 National Financial Well-Being Survey, this study examines how family structures, measured by marital status and the presence of financially dependent children, are associated with desirable financial behaviors, including day-to-day cash and credit management activities, the propensity to create and follow a financial plan, and the saving habits of American families. Empirical analyses revealed that family structure was significantly associated with family financial behaviors. Additionally, financial skills and both objective and subjective financial knowledge were significant factors. This paper provides a discussion of the key findings and their potential implications for financial therapists, financial planners, policymakers, and researchers interested in examining factors associated with enhancing beneficial family financial practices and bolstering family financial preparedness in the United States.
Keywords: family structure; financial behavior; financial skills; financial knowledge